2022
DOI: 10.1155/2022/7046208
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Does Income Inequality Harm Green Growth? The BRICS Experience

Abstract: Green growth plays a vital role in ensuring sustainable development. Managing economic growth without disrupting the environment is considered the need of the present time. Therefore, the empirics have turned their attention toward finding the determinants of green growth. Hence, we aim to investigate the impact of income inequality on green growth in BRICS economies from 1993 to 2020. Findings of the panel autoregressive distributed lag (ARDL) model confirm that the long-run estimate attached to GINI is negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Li et al (2022) also confirm IJDI 22,2 that inequality reduces environmental quality. Chen et al (2022) analyse, using panel ARDL estimation on data of BRICS, that income inequality significantly reduces green growth in India and China. Langnel et al (2021) examine the heterogeneous impact of income inequality on ecological footprint in West Africa.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Li et al (2022) also confirm IJDI 22,2 that inequality reduces environmental quality. Chen et al (2022) analyse, using panel ARDL estimation on data of BRICS, that income inequality significantly reduces green growth in India and China. Langnel et al (2021) examine the heterogeneous impact of income inequality on ecological footprint in West Africa.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%